FAO papers on selected issues relating to the WTO negotiations on agriculture (FAO. Commodities and Trade Division RomeIT, 2002)
Highlights some salient issues for consideration in the context of the WTO negotiations on agriculture in relation to incorporation food security concerns in a revised agreement. Examines the critical features of the agreement that may influence policy formulation for rural development. Argues that vulnerability to such shocks as external agricultural market instability and to import surges is of particular concern to developing countries that are endeavouring to develop their agricultural potential and diversify production in order to enhance their food security and alleviate poverty.
Keywords: AGRICULTURE